2015
DOI: 10.1007/s12178-015-9285-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of osteonecrosis of the femoral head with vascularized bone grafting

Abstract: Osteonecrosis of the femoral head (ONFH) is a challenging diagnosis for the patient and treating surgeon. Though its cause is poorly understood, several methods of surgical treatment exist and are performed with variable success. Vascularized bone grafting is one such treatment that attempts to restore viable bone, structural support, and blood supply to the avascular portion of the femoral head. This review summarizes the various approaches to this technique that have been proposed and put into practice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…For vascularized bone grafting, the fibula or iliac crest graft supports the subchondral bone with a viable, strong bone strut and enhances the revascularization of the femoral head. Free vascularized bone grafting is technically demanding, requires expertise in microsurgery, and is associated with donor site morbidity (Figures 7 - 8 ) [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…For vascularized bone grafting, the fibula or iliac crest graft supports the subchondral bone with a viable, strong bone strut and enhances the revascularization of the femoral head. Free vascularized bone grafting is technically demanding, requires expertise in microsurgery, and is associated with donor site morbidity (Figures 7 - 8 ) [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…It has been reported that between 5 and 40% of patients treated with long-term GC develop ON [3], and between 30 and 50% of patients develop GC-induced secondary osteoporosis [4]. In addition, GC-induced ON of the femoral head increases the risk of fractures and may lead to femoral head collapse, which often requires surgical treatments including total hip arthroplasty, bone grafting and osteotomy [2], [5], [6], [7]. Therefore, preclinical models of GC-induced ON that resemble the human pathology are useful for the development of novel and effective treatment modalities for patients with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, hip-preserving surgeries for ONFH mainly included core-decompression [9,10], vascularized or non-vascularized bone grafting [1,6,11,12], and osteotomy of the femur or acetabulum [13][14][15]. Hip-preserving surgery with vascularized pedicle iliac bone grafting (VPIBG) is an effective treatment for ONFH, which can reduce the intraosseous pressure, promote the revascularization of ischemic areas, provide structural support to prevent collapse [5,[16][17][18], and can be easily implemented without microsurgery techniques.…”
Section: Introductionmentioning
confidence: 99%